Berberine Acts on C/EBPβ/lncRNA Gas5/miR-18a-5p Loop to Decrease the Mitochondrial ROS Generation in HK-2 Cells - Xu, Jiang; Liu, Linqing; Gan, Lin; Hu, Yuanyuan; Xiang, Ping; Xing, Yan; Zhu, Jie; Ye, Shandong (Frontiers in Endocrinology, 2021)
Background: Berberine (BBR) has therapeutic effect on Diabetic nephropathy (DN), but its molecular mechanism is not completely clear. Methods: The DN model was established to observe the therapeutic effect of BBR. The expression levels of lncRNA Gas5 were detected by PCR. The transcriptional regulation of C/EBPβ on Gas5 was analyzed by ChIP-qPCR and luciferase reporter gene assay. The targeted regulation between Gas5 and miR-18a-5p and between miR-18a-5p and C/EBPβ 3 '- UTR was also analyzed. Results: In HG environment, BBR decreased the mitochondrial ROS generation and activated the C/EBPβ expression in HK-2 cells, C/EBPβ could combine with the reaction element on the promoter of Gas5 to promote its expression. Gas5 also inhibited the miR-18a-5p expression as ceRNA and reduce the negative regulatory effect of miR-18a-5p on C/EBPβ. BBR could activate C/EBPβ/PGC-1α signal pathway, regulate mitochondrial energy metabolism, inhibit ROS production and apoptosis by activating C/EBPβ/Gas5/miR-18a-5p positive feedback loop in HG environment. It also showed that BBR alleviated STZ induced renal injury in DN rats in vivo. Conclusions: This study suggested that BBR could regulate the mitochondrial ROS generation by activating the positive feedback loop of C/EBPβ/Gas5/miR-18a-5p.